Invasion origin, rapid population expansion, and the lack of genetic structure of cotton bollworm (Helicoverpa armigera) in the Americas. Issue 13 (17th June 2019) - Gonçalves, Rogério Martins; Mastrangelo, Thiago; Rodrigues, José Carlos Verle; Paulo, Daniel Fernando; Omoto, Celso; Corrêa, Alberto Soares; de Azeredo‐Espin, Ana Maria Lima
Abstract: In 2013, Helicoverpa armigera (Hübner) (Lepidoptera: Noctuidae) was officially declared as present in Brazil and, after two years, the species was detected in the Caribbean and North America. Information on genetic features and accurate distribution of pests is the basis for agricultural protection policies. Furthermore, such knowledge is imperative to develop control strategies, understand the geographical range, and genetic patterns of this species in the Americas. Here, we carried out the widest sampling of H. armigera in the South American continent and Puerto Rico, after we estimated the diversity, demographic parameters, and genetic structure. The Internal Transcribed Spacer 1 (ITS1) nuclear marker was used to investigate the presence of putative hybrids between H. armigera and H. zea, and they were observed at a frequency of 1.5%. An ABC analysis, based in COI gene fragment, suggested Europe as the origin of South America specimens of H. armigera and following a movement northward through the Caribbean. Three mtDNA genes and three nDNA markers revealed high genetic diversity distributed without the defined population structure of H. armigera in South America. Most of the genetic variation is within populations with a multidirectional expansion of H. armigera among morphoclimatic regions. High genetic diversity, rapid population expansion, and hybridization have implications for pest management since they suggest that adaptive alleles are spread through wide areas in South America that favor rapid local adaptation of H. armigera to new and disturbed environments (e.g., in agricultural areas). Abstract : This study presents the widest sampling for the pest Helicoverpa armigera in South America and Caribbean, where most of the regions sampled was not available for previous studies. We have performed classical population genetics investigations and an Approximate Bayesian Computation (ABC) analysis to investigate the geographical origin of this invasion in South America, besides to use Internal Transcribed Spacer 1 (ITS1) marker to assess the presence of hybrids between H. armigera and H. zea in Brazil.